Use of central nervous system drugs in combination with selective serotonin reuptake inhibitor treatment: a Bayesian screening study for risk of suicidal behavior - Lagerberg, T; Sjölander, A; Gibbons, RD; Quinn, PD; D'Onofrio, BM; Hellner, C; Lichtenstein, P; Fazel, S; Chang, Z (Frontiers Media, 2022)
Background: Using other central nervous system (CNS) medications in combination with selective serotonin reuptake inhibitor (SSRI) treatment is common. Despite this, there is limited evidence on the impact on suicidal behavior of combining specific medications. We aim to provide evidence on signals for suicidal behavior risk when initiating CNS drugs during and outside of SSRI treatment.